The wisdom and foolishness of God: First Corinthians 1-2 in theological exploration - Chalamet, Christophe; Askani, Hans-Christoph (Fortress Press, 2015)
The first two chapters of 1 Corinthians have played a significant role in the history of Christian theology. Interpreting the central event in Christianity, the crucifixion of Jesus, Paul reflects on the wisdom and foolishness of God in the “word of the cross.” This volume hopes to achieve two things by seeking to place exegetes, historians, philosophers, and theologians in conversation: to better understand Paul’s text and its reception and also to examine the ways in which it can nourish our theological reflection today